2014
DOI: 10.1021/nn505548n
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Ordered Nanopatterns for Spatial Control of Biomolecules

Abstract: The development and study of a benchtop, high-throughput, and inexpensive fabrication strategy to obtain hierarchical patterns of biomolecules with sub-50 nm resolution is presented. A diblock copolymer of polystyrene-b-poly(ethylene oxide), PS-b-PEO, is synthesized with biotin capping the PEO block and 4-bromostyrene copolymerized within the polystyrene block at 5 wt %. These two handles allow thin films of the block copolymer to be postfunctionalized with biotinylated biomolecules of interest and to obtain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…). During the irradiation, PMeOx was hypothesized to be degraded or released due to hydrolysis of the ester linkage in PMeOx ‐b‐ PS while PS is slightly crosslinked, which improving its fidelity upon subsequent processing . The thin films were then rinsed with acetic acid to remove the degraded byproducts of PMeOx and/or released PMeOx.…”
Section: Resultsmentioning
confidence: 99%
“…). During the irradiation, PMeOx was hypothesized to be degraded or released due to hydrolysis of the ester linkage in PMeOx ‐b‐ PS while PS is slightly crosslinked, which improving its fidelity upon subsequent processing . The thin films were then rinsed with acetic acid to remove the degraded byproducts of PMeOx and/or released PMeOx.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that regional annealing or deposition can provide good lateral variations in thin BCP films; however, these methods rely on the availability of sophisticated instrumentation . Chemical reactions of the BCP thin films were also investigated, such as photo‐crosslinking and hydrolysis, of one of the blocks . Although these reactions were shown to provide excellent spatial control over the morphologies, their general utility was limited.…”
Section: Methodsmentioning
confidence: 99%
“…Only a handful of examples for this approach can be found so far. 33,37,38 For instance, Lynn and co-workers reported the patterning of a fluorescent amine on a BCP nanostructured surface of which one block was entirely made of a custom, functional amine-reactive monomer unit. 38 Our idea is that it would be a more versatile method to employ a well-studied phase-segregating BCP system and introduce a functional comonomer during the synthesis in an amount that is (i) sufficient for further functionalization, (ii) yet low enough to preserve the phase behavior of the original, non-functional system.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies showed that small changes in structures can alter the morphologies and nanodomain periodicities, 39,40 a few reports suggested that incorporation of a small percentage (<10%) of functionalities into or at the end of the polymer backbones does not influence the phase separation behavior to a considerable extent. 37,[41][42][43][44] During the course of our study, Wiesner, Estroff, and co-workers have used such an elegant and versatile approach with a well-known phase-separating polystyrene-b-polyethylene glycol scaffold (PS-b-PEG), where a significant amount of allyl glycidyl ether was introduced in the PEG block to provide allyl anchors for further thiol-ene-based functionalization. 45 Nevertheless, only one type of functionality was reported and, in fact, the polymerization method which was used, i.e., anionic polymerization, may limit the range of accessible functionalities.…”
Section: Introductionmentioning
confidence: 99%